Effective Removal of Fluoride onto Metal Ions Loaded Orange Waste - Ghimire, Kedar Nath (Journal of Nepal Chemical Society, 2012)
Removal of fluoride is investigated onto several metal ions loaded phosphorylated orange juice residue and commercially available alumina. The experimental results revealed that cerium (IV) loaded phosphorylated orange waste indicated excellent fluoride removal efficiency at acidic pH range and while that lanthanum loaded at neutral pH range. Both the metal loaded adsorbents are found superior to the commercially available activated alumina. DOI: http://dx.doi.org/10.3126/jncs.v27i1.6660 J. Nepal Chem. Soc., Vol. 27, 2011 61-66